“Analysis of Speaking Skills in Students' Social Interaction” (Case Study of Interactive Approach in the Classroom) - Joko Setiyono; Abdul Ghoni Asror; Anik Puspitasari; Muhamad Sholehhudin (Proceeding International Conference on Digital Education and Social Science, 2024)
This study aims to analyze the implementation of an interactive approach in students' social interactions and its impact on speaking skills in the Indonesian Language and Literature Education Program (PBSI) at IKIP Bojonegoro. The research employs a descriptive qualitative method, with data collected through observations and interviews. The results indicate that the application of the interactive approach creates a dynamic and participative learning environment. During the learning process, students engage in group discussions, role-playing, and other collaborative activities. This not only enhances their speaking skills but also encourages critical thinking and the exchange of ideas. Classroom observations reveal that students are more willing to express their opinions and ask questions, which had previously been a challenge for them. From the interviews, students reported feeling more motivated and confident when speaking in public after participating in these interactive activities. Additionally, the social interactions that occurred during the learning process strengthened relationships among students, creating a more familiar and supportive classroom atmosphere. Thus, the interactive approach proves effective in improving students' speaking skills as well as enhancing the quality of social interactions within the classroom.